Analisis Comfort dan Kualitas Tidur Orang Dengan HIV/AIDS - Ahmad Ikhlasul Amal; Retno Issroviatiningrum (Poltekkes Kemenkes Maluku, 2022)
The case of HIV (Human Immunodeficiency Virus)/AIDS (Acquired Immuno Deficiency Syndrome) is not only a problem in Indonesia but has reached the global area. This affects the basic needs of people living with HIV/AIDS (PLWHA) ranging from physical needs, a sense of security, comfort, self-actualization, and especially sleep. PLWHA often experience sleep disturbances so which can cause a lack of sleep quality. PLWHA Comfort is a matter of concern in achieving quality sleep. It is necessary to identify the correlation of comfort of and sleep quality. This study aims to determine the correlation of comfort and sleep quality of among HIV/AIDS patients. This study used a cross-sectional approach involving 68 respondents through purposive sampling. The instruments used are the Shortened General Comfort Questionnaire (SGCQ) and the Pitsburg Sleep Quality Index (PSQI). Bivariate analysis using the Spearman test obtained a p-value of 0.019 (<0.05). The conclusion of this study is that there is a relationship between comfort and sleep quality of PLWHA. Attention is needed in efforts to improve the quality of sleep of PLWHA by paying attention to the comfort aspect. Future research can explore other related factors or the development of nursing interventions.